The Effect of Patin Fish Oil Extract on LDL Cholesterol Levels Rattus norvegicus was Induced by Alloxan - Salsabila Yumna Fathony; Fitri Handajani; Indri Ngesti Rahayu (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Diabetes mellitus is a chronic hyperglycemic syndrome that can be accompanied by lipid metabolism disorders. Alloxan is a diabetogenic agent that is associated with an increase in LDL cholesterol levels. Patin fish contain omega-3 and oleic acid, which can potentially reduce or control LDL cholesterol levels. This study aims to determine the effect of Patin fish (Pangasius hypothalmus) oil extract on LDL cholesterol levels of alloxan-induced Rattus norvegicus. The method of this study is the post-test-only control group design. Twenty-seven experimental animals were divided into 3 groups; (1) the 1st group was without treatment, (2) 2nd group was induced with 150 mg/kg BW alloxan on the 7th day; (3) 3rd group was induced with 150 mg/kg BW alloxan on the 7th day and given the Patin fish oil extract at a dose of 73 mg/kg BW on the 10th day for 14 days. Blood samples were taken on the 24th day to determine LDL cholesterol levels. The results of the One-Way ANOVA test showed a significant mean difference, p=0,001 (p<a). The results of the Post-Hoc LSD test showed a meant difference between the 1st group and the 2nd control group p=0,001 (p<a); 2nd group and 3rd group p=0,026 (p<a); between the 1st group and the 3rd group p=0,015 (p<a). Giving alloxan 150 mg/kg BW can significantly increase LDL cholesterol levels of Rattus norvegicus and administration of Patin fish oil extract 73 mg/kg BW can significantly reduce LDL cholesterol levels of Rattus norvegicus.